2011
DOI: 10.1007/s11250-011-9806-4
|View full text |Cite
|
Sign up to set email alerts
|

Physical, chemical and sensorial parameters for lambs of different groups, slaughtered at different weights

Abstract: The object of this experiment was to study physicochemical and sensorial traits in the 11th and 13th ribs of 24 Santa Ines (SI), 24 1/2 Ile de France × 1/2 Santa Inês (ILE × SI) and 8 1/2 Texel × 1/2 Santa Inês (TE × SI), slaughtered at different weights (30, 35, 40 and 45 kg, respectively). Subjective measurements (marbling, colour and texture) were carried out on the Longissimus dorsi, as well as initial pH (0 h) and final pH (24 h) after slaughter. The experiment was in a 3 × 4 factorial design and analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
3
14
1
Order By: Relevance
“…Final live weight influenced skin thickness total area and the height measured by ultrasound (P<0.05). Landim et al (2011), in a study with male and female crossbred Santa Inês at different slaughter weights, found values for fat thickness for females slaughtered at 30 kg close to those found in this study. Cardoso (2008), working with different breed groups and slaughter weights, obtained FI between 3.61 and 3.42 for female Santa Ines animals.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Final live weight influenced skin thickness total area and the height measured by ultrasound (P<0.05). Landim et al (2011), in a study with male and female crossbred Santa Inês at different slaughter weights, found values for fat thickness for females slaughtered at 30 kg close to those found in this study. Cardoso (2008), working with different breed groups and slaughter weights, obtained FI between 3.61 and 3.42 for female Santa Ines animals.…”
Section: Resultssupporting
confidence: 88%
“…Cardoso (2008), working with different breed groups and slaughter weights, obtained FI between 3.61 and 3.42 for female Santa Ines animals. Landim et al (2007) found 2.77; Bueno et al (2001), 1.82;and Furusho-Garcia et al (2003) found average of 2.4 for FI, i.e., all values were lower than this study.…”
Section: Resultscontrasting
confidence: 58%
See 3 more Smart Citations